2004
DOI: 10.1124/mol.65.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Salvinal, a Novel Microtubule Inhibitor Isolated from Salvia miltiorrhizae Bunge (Danshen), with Antimitotic Activity in Multidrug-Sensitive and -Resistant Human Tumor Cells

Abstract: Aqueous extracts of Salvia miltiorrhizae Bunge have been extensively used in the treatment of cardiovascular disorders and cancer in Asia. Recently, a compound, 5-(3-hydroxypropyl)-7-methoxy-2-(3Ј-methoxy-4Ј-hydroxyphenyl)-3-benzo[b]furancarbaldehyde (salvinal), isolated from this plant showed inhibitory activity against tumor cell growth and induced apoptosis in human cancer cells. In the present study, we investigated the cytotoxic effect and mechanisms of action of salvinal in human cancer cell lines. Salvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 31 publications
3
49
0
2
Order By: Relevance
“…As previously reported, 6-hour paclitaxel treatment significantly increased polymerized tubulin in EBC-1 cells. In contrast, vincristine treatment decreased assembled microtubules (31). As expected, tivantinib treatment inhibited tubulin polymerization in a concentration-dependent manner similar to that by vincristine treatment but surprisingly did not inhibit c-MET and its downstream AKT and ERK signaling pathways.…”
Section: Tivantinib Inhibited Tubulin Polymerization In Cellssupporting
confidence: 69%
“…As previously reported, 6-hour paclitaxel treatment significantly increased polymerized tubulin in EBC-1 cells. In contrast, vincristine treatment decreased assembled microtubules (31). As expected, tivantinib treatment inhibited tubulin polymerization in a concentration-dependent manner similar to that by vincristine treatment but surprisingly did not inhibit c-MET and its downstream AKT and ERK signaling pathways.…”
Section: Tivantinib Inhibited Tubulin Polymerization In Cellssupporting
confidence: 69%
“…Previous reports indicated that several chemicals regulated the Cdc2/cyclinB complex and arrest cell cycle in G2-M phase through Cdc25C and Myt-1 proteins. The elevated hyperphosphorylation of Cdc25C and declined unphosphorylated Cdc25C (interphase Cdc25C) in human cancer cells were parallel with the activation of Cdc2/cyclinB after exposure of chemicals Chang et al, 2004;Kuo et al, 2004;Singh et al, 2004]. Griseofulvin, an anti-fungal agent caused the down-regulation of Myt-1 protein expression, contributed the abnormal G2-M cell cycle arrest [Ho et al, 2001].…”
Section: Discussionmentioning
confidence: 96%
“…Multidrug resistance and DNA repair are of prime concern with DNA alkylating agents. 7,8 Intriguingly, BO-1090 was more effective in Taxol-and vincristine-resistant KB cell lines (Supporting Information Table 4), which exhibit the pg170/ MDR1 resistance phenotype, 14 than in parental KB cells. The resistance ratio (ratio of IC50 of resistant to parental cell) of BO-1090 was 0.93 for Taxol-resistant and 0.731 for vincristine-resistant cells, indicating that BO-1090 may bypass the MDR1 effect.…”
Section: Cancer Therapymentioning
confidence: 98%